1991
DOI: 10.1111/j.1755-3768.1991.tb04815.x
|View full text |Cite
|
Sign up to set email alerts
|

Gonioscopic findings in Greek patients with exfoliation glaucoma

Abstract: A prospective gonioscopic evaluation was carried out upon a cohort of Greek patients who had undergone trabeculectomy for open-angle glaucoma. Sixty-five patients were found to show clinical evidence of exfoliation glaucoma (EXG), whilst nine patients were deemed to have primary open angle glaucoma (POAG). The gonioscopic features of these eyes and of 43 non-operated eyes from the same patients with either exfoliation syndrome (EXS) or EXG are presented. The median degree of angle pigmentation was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
4
0
6
Order By: Relevance
“…T h e close relation between PEX and IOP disturbances, was also proved by checking the mean IOP in the eyes with unilateral PEX. In the affected PEX-eye, the mean IOP was increased more than 2.0 mmHg and this is consistent with previous analogous studies (Aasved 1971;Kozart & Yanoff 1982, Madden & Crowley 1982Sugar 1984;Konstas & Dutton 1991;Stefaniotou et al 1990).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…T h e close relation between PEX and IOP disturbances, was also proved by checking the mean IOP in the eyes with unilateral PEX. In the affected PEX-eye, the mean IOP was increased more than 2.0 mmHg and this is consistent with previous analogous studies (Aasved 1971;Kozart & Yanoff 1982, Madden & Crowley 1982Sugar 1984;Konstas & Dutton 1991;Stefaniotou et al 1990).…”
Section: Discussionsupporting
confidence: 92%
“…The abnor- malities of the iris vessels (Vannas 1969;Konstas et al 1991) precede the clinical features, i.e. an increased quantity of pigment may be clinically observed in the anterior segment (Sugar 1984;Konstas & Dutton 1991). For this reason the term 'clinically unilateral pseudoexfoliation' is accurately used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has now been suggested that the pigmentary signs not only accompany, but precede the fully established condition (Wishart et al 1985;Jerndal 1986;Prince et al 1987;Rouhiainen & Terasvirta 1990;Konstas & Dutton 1991). Therefore, these signs not only facilitate the diagnosis of the disorder, but more significantly may even predict its development.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation in the angle is also often increased but irregular. [49][50][51][52]62,[64][65][66][67][68][69][70][71][72][73][74][75][76] Additional pigmentation is observed along Schwalbe line, termed a "Sampaolesi's line." 72,73,77 This finding is not exclusive to PXF, but can be seen in pigment dispersion syndrome and chronic inflammation.…”
Section: Anglementioning
confidence: 99%